Smart & Green Tourism In Bali: Integrating Digital Technologies And Circular Economy Principles For A Low-Carbon Destination Development - Christianto, Jery; Alit Adinugraha, Dewa Made (Politeknik Internasional Bali, 2025)
This study examines the integration of digital technologies and circular economy principles to support Bali’s transition toward a low-carbon tourism destination. Employing a qualitative descriptive approach with secondary data analysis, the research synthesizes evidence from academic literature, government policies, and industry reports to explore how smart and green tourism can be effectively operationalized. The findings demonstrate that digital technologies including IoT, big data, artificial intelligence, and VR/AR play a pivotal role in improving energy efficiency, optimizing transportation flows, enabling smart waste management, and preserving cultural heritage, while simultaneously enhancing visitor experiences and destination competitiveness. In parallel, circular economy practices such as waste reduction, recycling, eco-design, and resource efficiency address pressing environmental challenges while also strengthening local economies, cultural industries, and community resilience. Despite progress, Bali’s implementation remains partial and fragmented, constrained by weak market demand for eco-friendly products, limited infrastructure, and low community literacy regarding sustainability practices. Theoretically, this study enriches sustainable tourism literature by advancing an integrative framework that connects smart and green paradigms. Practically, it offers strategic insights for policymakers, industry stakeholders, and local communities to enhance competitiveness while safeguarding cultural identity and ecological sustainability. The study concludes that Bali’s pathway to sustainable tourism requires stronger regulations, fiscal incentives, digital literacy programs, and collaborative governance to build a holistic low-carbon ecosystem.